👤

Rozwiąż równania

a) 4x + 5 = 2x – 7

b) -3x +8 = 2x + 7

c) 3(y+ 2) = -2(y - 3)

d) 3x -7 = 27x + 11

e) 8 - 3x2 = 3x *(2 - x) -2x

f) (x + 3)(x - 4) = (x +2)(x - 1)
plis o szybką odpowiez


Odpowiedź :

a)4x - 2x = -7 -5
2x=-12: 2
x= -6

b)-3x - 2x = 7 + 8
-6x = 15 : (-6)
x= -2,5

c)3y +6 = -2y +6
3y + 2y = 6-6
5y=0 : 5
y=0


d)3x-27x = 11 + 7
-24x = 18: (-24)
x= - 3/4

e) 8 - 3x2 = 6x - 3x2 -2x
-6x+2x=-8
-4x= -8 : (-4)
x= 2


f) x2 -4x +3x -12 = x2 -x +2x -2
-4x + 3x + x -2x = -2 +12
-2x= 10 : (-2)
x= -5
a) 4x+5=2x-7 |-5
4x+5-5=2x-7-5
4x=2x-12 |-2x
4x-2x=2x-12-2x
2x=-12 |:2
x=-6

b) -3x+8=2x+7 |-8
-3x+8-8=2x+7-8
-3x=2x-1 |-2x
-3x-2x=2x-1-2x
-5x=-1 |:(-5)
x=0,2

c) 3(y+2)=-2(y-3)
3y+6=-2y+6 |-6
3y+6-6=-2y+6-6
3y=-2y |+2y
3y+2y=-2y+2y
5y=0 |:5
y=0

d) 3x-7=27x+11 |+7
3x-7+7=27x+11+7
3x=27x+18 |-27x
3x-27x=27x+18-27x
-24x=18 |:(-24)
x=-0,75

e) 8-3x[2]=3x(2-x)-2x
8-3x[2]=6x-3x[2]-2x |+3x[2]
8-3x[2]+3x[2]=6x-3x[2]-2x+3x[2]
8=6x-2x
8=4x
4x=8 |:4
x=2

f) (x+3)(x-4)=(x+2)(x-1)
x[2]-4x+3x-12=x[2]-x+2x-2 |-x[2]
x[2]-4x+3x-12-x[2]=x[2]-x+2x-2-x[2]
-4x+3x-12=-x+2x-2
-x-12=x-2 |+12
-x-12+12=x-2+12
-x=x+10 |-x
-x-x=x+10-x
-2x=10 |:(-2)
x=-5

On Studier: Inne Pytanie